Trace gas and aerosol interactions in the fully coupled model of aerosol-chemistry-climate ECHAM5-HAMMOZ: 1. Model description and insights from the spring 2001 TRACE-P experiment - Pozzoli, L; Bey, I; Rast, S; Schultz, MG; Stier, P; Feichter, J (2008)
In this paper, we introduce the ECHAM5-HAMMOZ aerosol-chemistry-climate model that includes fully interactive simulations of Ox-NOx-hydrocarbons chemistry and of aerosol microphysics (including prognostic size distribution and mixing state of aerosols) implemented in the General Circulation Model ECHAM5. The photolysis rates used in the gas chemistry account for aerosol and cloud distributions and a comprehensive set of heterogeneous reactions is implemented. The model is evaluated with trace gas and aerosol observations provided by the TRACE-P aircraft experiment. Sulfate concentrations are well captured but black carbon concentrations are underestimated. The number concentrations, surface areas, and optical properties are reproduced fairly well near the surface but underestimated in the upper troposphere. CO concentrations are well reproduced in general while O3 concentrations are overestimated by 10-20 ppbv. We find that heterogeneous chemistry significantly influences the regional and global distributions of a number of key trace gases. Heterogeneous reactions reduce the ozone surface concentrations by 18-23% over the TRACE-P region and the global annual mean O3 burden by 7%. The annual global mean OH concentration decreases by 10% inducing a 7% increase in the global CO burden. Annual global mean HNO3 surface concentration decreases by 15% because of heterogenous reaction on mineral dust. A comparison of our results to those from previous studies suggests that the choice of uptake coefficients for a given species is the critical parameter that determines the global impact of heterogeneous chemistry on a trace gas (rather than the description of aerosol properties and distributions). A prognostic description of the size distribution and mixing state of the aerosols is important, however, to account for the effect of heterogeneous chemistry on aerosols as further discussed in the second part of this two-part series. Copyright 2008 by the American Geophysical Union.